1984
DOI: 10.1111/j.1471-4159.1984.tb02715.x
|View full text |Cite
|
Sign up to set email alerts
|

58,000 Dalton Intermediate Filament Proteins of Neuronal and Nonneuronal Origin in the Goldfish Visual Pathway

Abstract: A group of proteins in the goldfish optic nerve with a molecular weight of 58K daltons was analyzed by two-dimensional gel electrophoresis. Results show that the proteins are differentially phosphorylated and found exclusively in a cytoskeletal-enriched fraction. The proteins from this fraction can be reconstituted into typical intermediate filament structures, as shown by electron microscopy. Two components which are of neuronal origin are transported within the slow phase of transport. The 58K proteins are t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
61
1

Year Published

1986
1986
1997
1997

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 48 publications
(49 reference statements)
8
61
1
Order By: Relevance
“…lA), as previously reported (Nona et al, 1989;Quitschke and Schechter, 1984;Quitschke et al, 1980). Two major protein bands were apparent at 48 kDa and 58 kDa, while the presence of a 51 kDa band, corresponding to GFAP, was not readily recognisable.…”
Section: Normal Goldfishsupporting
confidence: 75%
“…lA), as previously reported (Nona et al, 1989;Quitschke and Schechter, 1984;Quitschke et al, 1980). Two major protein bands were apparent at 48 kDa and 58 kDa, while the presence of a 51 kDa band, corresponding to GFAP, was not readily recognisable.…”
Section: Normal Goldfishsupporting
confidence: 75%
“…5b), not glia. Bands 2 and 3 are probably equivalent to the 58 kDa complex of axonal and glial proteins found in goldfish optic nerve (Quitschke and Schechter, 1984), and in agreement, Ab2 and Ab3 recognized optic axons and astroglia, respectively, in the goldfish.…”
Section: Anatomical Synopsissupporting
confidence: 75%
“…Previous biochemical (Quitschke and Schechter, 1984) and histological (Jones et al, 198613) results showed that gefiltin is the predominant neurofilament protein in the goldfish optic nerve, whereas plasticin was a minor neurofilament protein. Both were synthesized in ganglion cells and transported into the optic nerve within the slow phase of axonal transport (Quitschke and Schechter, 1984;Glasgow et al, 1992).…”
mentioning
confidence: 97%
“…Both were synthesized in ganglion cells and transported into the optic nerve within the slow phase of axonal transport (Quitschke and Schechter, 1984;Glasgow et al, 1992). During regeneration following optic nerve crush, the rates of mRNA accumulation for gefiltin…”
mentioning
confidence: 99%